Panitikan a video documentary on Philippine literature (Tuklas Sining, 1989)
Traces the origins and development of Philippine literature from the oral riddles, chants and the tanaga through the pasyon and awit of Spanish colonial literature, to the poetry and prose of the 19th century nationalist writers, to the classic 20th century romanticism, realism and radicalism.